FADD promotes type I interferon production to suppress porcine reproductive and respiratory syndrome virus infection - Chang, Xiaobo; Wang, Mengqi; Li, Zhaopeng; Wang, Lei; Zhang, Gaiping; Chang, Yafei; Hu, Jianhe (Frontiers in Veterinary Science, 2024)
Porcine reproductive and respiratory syndrome (PRRS) is an epidemic animal infectious disease worldwide, causing huge economic losses to the global swine industry. Fas-associated death domain (FADD) was previously reported to be an adaptor protein that functions in transferring the apoptotic signals regulated by the death receptors. In the current study, we unravel its unidentified role in promoting type Ⅰ interferon (IFN) production during PRRS virus (PRRSV) infection. We identified that FADD inhibited PRRSV infection via promotion of type Ⅰ IFN transcription. Overexpression of FADD suppressed the replication of PRRSV, while knockout of FADD increased viral titer and nucleocapsid protein expression. Mechanistically, FADD promoted mitochondrial antiviral signaling protein (MAVS)-mediated production of IFN-β and some IFN-stimulated genes (ISGs). Furthermore, FADD exerted anti-PRRSV effects in a MAVS-dependent manner and increased the type Ⅰ IFN signaling during PRRSV infection. This study highlights the importance of FADD in PRRSV replication, which may have implications for the future control of PRRS.